On some fixed point theorems in Banach spaces - D. V. Pai; P. Veeramani (International Journal of Mathematics and Mathematical Sciences)
In this paper, some fixed point theorems are proved for multi-mappings as well as a pair of mappings. These extend certain known results due to Kirk, Browder, Kanna, Ćirić and Rhoades.